Market Segmentation, Customers, and Value Propositions Analysis for Polymer Clay Art Business Start-Up - Hidayat, Desman; Suci, Apriani Kurnia; Saliha, Gita Khadijatu (Bina Nusantara University, 2016)
Polymer clay art is one of the creative businesses that are recently starting to get a lot of attentions. To prepare a startup business in this field, analysis from a lot of aspects is needed. The purpose of this article was to explain the approach of the polymer clay art business startup from the market segmentation, customer, and value proposition side of the business. The method was applied by analyzing those steps in details. The analysis started from brainstorming to choose the market matching to business, the customer side, value proposition, and between both aspects. The result of the analysis shows the business focus of the polymer clay art business, where the value propositions are focusing on unique decorations, and several types of customer segments.